Menaklukkan Dan Memelihara Bumi: Kajian Teologis Mengenai Tugas Manusia Berdasarkan Dokumen Gereja Huria Kristen Batak Protestan (HKBP) - Nainggolan, Hanna Yohana; Marpaung, Frans Best Soma; Harianja, Mikael; Hasibuan, Ricky Pramono (Sekolah Tinggi Teologi Berea, Salatiga, 2023)
This article explores a comparison between the positive ideals presented in the Bible regarding the creation of the Earth and the current reality where the Earth is confronted with various environmental challenges such as pollution and climate crises. Although the Bible teaches that humans bear the responsibility of caring for and wisely using Earth's resources, the present reality reveals that human activities are causing environmental harm. Building upon this, the article delves into the meaning of humanity's task to subdue and cultivate the Earth, as outlined in Genesis 1:28. Employing a qualitative approach, the author intricately examines theological perspectives and documents from the Protestant Christian Batak Church (HKBP) to comprehend and apply the responsibility of preserving and nurturing the Earth. The emphasis is placed on the notion that involvement in these efforts extends beyond a global duty, encompassing a personal and familial calling to ensure the sustainability of the Earth as God's creation.